Producción del pasto Carimagua I (Andropogon gayanus), con fertilización orgánica. - Alanuca Maiquiza, Jairo David (2022)
This research project was carried out at the Sacha Wiwa Experimental Center, Guasaganda village, La Maná canton, in the province of Cotopaxi, where the following objectives were set: To determine the agronomic response of Carimagua I grass (Andropogon gayanus). To analyze the production of Carimagua I grass (Andropogon gayanus) with the application of organic fertilizers biol and earthworm humus. To know the costs of the treatments understudy for the production of Carimagua I grass (Andropogon gayanus). The treatments used were T1 = Control, T2 = Biol, T3 = Worm humus, T4 = Biol + Worm humus. The Completely Randomized Block Design (CSBD) was used with 4 treatments and 6 replicates. Tukey's multiple range test was applied at 5 % statistical probability. The variables of plant height, green forage production weight, foliar analysis, establishment costs, and pasture production were evaluated. The soil presented a pH of 5.60, which gave a result of Medium Acid, its level of organic matter is 3.20 % medium, and the textural class of the soil is sandy loam. The biol and worm humus presented a concentration in % of nitrogen, phosphorus, potassium, calcium, magnesium, low sulfur; boron, zinc, copper, and only high iron and manganese in medium ppm. The greatest grass height was achieved with the Biol + Worm humus treatment with a height of 55.17 cm; Worm humus with 133.08 cm and 219.05 cm at 21, 42, and 63 days respectively. The highest green forage production in 12 m² was achieved with the Worm humus treatment with a weight of 106.16 g, 815.97 g, and 941.64 g at 21, 42, and 63 days respectively. The highest green forage and dry matter production in kilograms per hectare were obtained with the Worm humus treatment with a weight of 88.47 kg FV ha; 22.12 kg DM ha, 679.98 kg FV ha; 169.99 kg DM ha, and 784.70 kg FV ha; 196.18 kg DM ha at 21, 42, and 63 days respectively. The highest protein percentage was obtained at 21 days with 14.53 %. The costs of establishment and production per m² of Carimagua I grass (Andropogon gayanus) amounted to 1.12 US dollars, which makes it feasible to establish a bank of this grass for forage production.